Fluorescence diagnostics of dental caries - L. S. Lyashenko; M. P. Samtsov; E. S. Voropay; A. V. Butvilovski; V. R. Gaifullina; M. V. Bobkova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results obtained in studies of laser-induced fluorescence of the normal and carries-affected dental tissues are presented. The possibility of detection of considerable depth caries with use of the specially designed spectrometric system with excitation by a semiconductor laser source with a wavelength of 684 nm for fluorescence is shown.